“Y lo de viejo, sintiéndolo mucho”. Ambiguity, Old Age, Tone and Pose? in “Sintiéndolo mucho” by Joaquín Sabina (Anclajes, 2026)
Since the release of the album Lo niego todo (2017) up to the present day, old age as a topic has acquired a central space in Joaquín Sabina's poetics, allowing for the construction of new facets of his authorial image. However, old age does not operate exclusively in this authorial project as the manifestation of a biological age, but also functions as a machinery for producing new fictions. On this occasion, we will approach the song "Sintiéndolo mucho" (2022) —the theme music for the eponymous film by Fernando León— from the platform offered by old age understood in terms of the closure or ending of an authorial project. Paradoxically, this old age finds a fertile ground for the production of new artistic creations and for the consolidation of a singular mythology surrounding the authorial persona in the liminal spaces of a voice that declares itself to be in retreat.
Keywords: Joaquín Sabina; Old Age; Authorial Project; Singer-songwriter Music; Spanish Poetry